Limites probatórios da delação premiada frente à verdade no processo penal - Mandarino, Renan Posella [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The evidence in the criminal procedure is produceded by analog reconstruction of facts bt the parties and collaborators of justice, through the perception and individual interpretation about particular reality. The truth is linked to the production procedure evidence, so that the criminal prosecution is oriented by the “need” to reach the truth. However, this search for truth collides with the constitucional, legal and linguistic limits. The plea bargaining are collaborative investigative techniques used to unveil the crimes of high complexity. Its ai mis to promote the participarion of the accused in the search for truth. The main objective of this research is to analyse the evidentiary limits os plea bargaining front to the formartion of truth in criminal procedure. To examine the problem proposed, in the first chapter, the criminal procedure is contextualized in the contemporary society, filled with risk and State efficiency. In the second chapter, find out system proof anda the formation os truth in criminal procedure. Then, the investigantion focuses on the legal nature and the rules concerning the plea bargaining, including negotiation model and american influences in the brazilian cirminal procedure system. Finally, it examines the limits to the use of the premial agreements are submittes in the lawsuit. The procedural methology is the bibliographical anda the method of approach is the hypothetical-deductive. One hypothesis suggests that, from the use of plea bargaining, agreements have been established a new truth procedure, negoating character. To assume the plea bargaining institute in the contexto of posmodern society, the conclusion of reach is that the negoating model guides the search for truth in the process, but not only that. The purpose of pacts premials goes beyond the pursuit of truth, because it aims to also manage the risk in social systems.

A prova no processo penal é produzida através da reconstrução analógica dos fatos pelas partes, juiz e colaboradores da justiça, através da percepção e interpretação individual sobre determinada realidade. A verdade processual está vinculada à produção probatória, de maneira que a persecução penal se orienta pela “necessidade” de alcançar a verdade. Entretanto, a busca pela verdade colide com os limites constitucionais, legais e linguísticos. Os acordos de delação premiada são técnicas investigativas colaborativas utilizadas para desvelar crimes de alta complexidade. Seu intuito é promover a participação dos acusados na busca da verdade. O objetivo central da pesquisa é a análise dos limites probatórios da delação premiada frente à formação da verdade no processo penal. Para examinar o problema proposto, necessário contextualizar o processo penal no cenário da sociedade contemporânea, permeada esta pelo risco e eficientismo, e esmiuçar o sistema de provas utilizado para a formação da verdade. Há a investigação da natureza jurídica e das normas referentes à colaboração premiada, com destaque para o modelo negocial e as influências norteamericanas no sistema processual penal brasileiro, analisando os limites probatórios a que os acordos premiais estão submetidos no processo judicial. A metodologia procedimental é a bibliográfica e o método de abordagem é o hipotético-dedutivo. A hipótese trabalhada é a de que, a partir da utilização dos acordos de delação premiada, teria sido estabelecida uma nova verdade processual, de caráter negocial. Ao assumir que o instituto da colaboração premiada se insere no contexto da sociedade pós-moderna, a conclusão a que se chega é que o modelo negocial orienta a busca da verdade no processo, porém, não apenas isso. A finalidade dos pactos premiais vai além da busca da verdade, pois almeja também gerenciar os riscos nos sistemas sociais.
Evedentiary limits of plea bargaining front of criminal procedure
Keywords: Delação premiada; Verdade; Risco; Justiça penal negocial; Garantias processuais; Plea bargaining; Truth; Risk; Negotial criminal justice; Procedural guarantees